Dampak Kebijakan Persusuan di Indonesia Terhadap Kesejahteraan Stakeholder - Agustia, Devi; Fitri, Annisa; Andriyanty, Reny; Suryadi, Didik; Maifianti, Khori Suci; Sirait, Sudirman (Universitas Galuh, 2026)
Indonesia’s dairy industry has undergone substantial development over the past decade, yet it continues to face persistent challenges arising from market liberalization and intensifying global competition. The BUSEP ratio policy, introduced in 1982, was designed to protect smallholder dairy farmers by mandating the absorption of domestically produced fresh milk by processing industries. This study aims to systematically examine the impacts of this policy on the welfare of key stakeholders: government, producers, and consumers, while also identifying the resulting economic and social implications. The research employs a systematic literature review combined with static comparative analysis using secondary data. Comparisons are drawn between conditions before and after the abolition of the BUSEP ratio policy, with specific attention to changes in producer surplus and consumer surplus. In addition, the study assesses the influence of a 5% import tariff on domestic milk pricing structures and supply conditions. The findings reveal that while the BUSEP ratio policy increased producer surplus, it significantly reduced consumer surplus, ultimately leading to a decline in net social welfare. The policy’s revocation in 1998 did not yield the anticipated benefits, as import prices surged sharply during the monetary crisis, preventing processors from optimizing alternative supply sources. Heightened competition with international producers further underscores the need for domestic farmers to enhance efficiency and competitiveness. Overall, the study indicates that existing policies have not optimally improved welfare outcomes. Consequently, there is a pressing need for more adaptive policy frameworks that prioritize production efficiency, price stability, and sustained protection for Indonesia’s dairy farmers.